Evidence that sigma factors are components of chloroplast RNA polymerase. - Troxler, R F (1994)
Plastid genes are transcribed by DNA-dependent RNA polymerase(s), which have been incompletely characterized and have been examined in a limited number of species. Plastid genomes contain rpoA, rpoB, rpoC1, and rpoC2 coding for alpha, beta, beta', and beta" RNA polymerase subunits that are homologous to the alpha, beta, and beta' subunits that constitute the core moiety of RNA polymerase in bacteria. However, genes with homology to sigma subunits in bacteria have not been found in plastid genomes. An antibody directed against the principal sigma subunit of RNA polymerase from the cyanobacterium Anabaena sp. PCC 7120 was used to probe western blots of purified chloroplast RNA polymerase from maize, rice, Chlamydomonas reinhardtii, and Cyanidium caldarium. Chloroplast RNA polymerase from maize and rice contained an immunoreactive 64-kD protein. Chloroplast RNA polymerase from C. reinhardtii contained immunoreactive 100- and 82-kD proteins, and chloroplast RNA polymerase from C. caldarium contained an immunoreactive 32-kD protein. The elution profile of enzyme activity of both algal chloroplast RNA polymerases coeluted from DEAE with the respective immunoreactive proteins, indicating that they are components of the enzyme. These results provide immunological evidence for sigma-like factors in chloroplast RNA polymerase in higher plants and algae.